Carbon taxes from an economic perspective - Österreichisches Institut für Wirtschaftsforschung, Vienna; Kettner-Marx, Claudia; Kletzan-Slamanig, Daniela (Vienna, 2018)
"Economic literature generally favours market-based instruments for regulating environmental externalities since they ensure compliance at the least cost to society. Emission taxes have been increasingly introduced internationally, with the focus shifting to CO2 after the adoption of the Kyoto Protocol in 1997. In this paper, the theoretical economic literature on energy and emission taxes is reviewed. The focus is on theoretical recommendations regarding the optimal design of environmental and especially carbon taxes, their performance relative to other instruments, the concept of a double dividend as well as potential competitiveness and distribution effects. Carbon taxation can play a key role in climate policy and for achieving long-term emission reductions. This overview of economic considerations may help in creating a sustainable, effective and efficient regulatory system for reducing emissions."